(untitled) (Pulse, 2015)
Congenital dermoid inclusion cyst over the anterior fontanelle (CDIC) is an uncommon cystic lesion. It is a benign and curative lesion. In these two cases a soft, cystic mass located over the anterior fontanelle. The cyst had no intracranial extension and was easily excised intact. The clinical and image findings of the cysts were described and compared with the usual dermoids. Many different types of lesions over the children’s skull exist and some are commonly diagnosed in daily practice. Congenital dermoid inclusion cyst over the anterior fontanelle (CDIC) is a rare and benign lesion. Pulse Vol.7 January-December 2014 p.42-45